Impact of Patient Age on Molecular Alterations of Left‐Sided Colorectal Tumors. (17th July 2018) - Puccini, Alberto; Lenz, Heinz‐Josef; Marshall, John L.; Arguello, David; Raghavan, Derek; Korn, W. Michael; Weinberg, Benjamin A.; Poorman, Kelsey; Heeke, Arielle L.; Philip, Philip A.; Shields, Anthony F.; Goldberg, Richard M.; et al.
Abstract: Background: The incidence of colorectal cancer (CRC) in younger patients is rising, mostly due to tumors in the descending colon and rectum. Therefore, we aimed to explore the molecular differences of left‐sided CRC between younger (≤45 years) and older patients (≥65). Subjects, Materials, and Methods: In total, 1, 126 CRC tumor samples from the splenic flexure to (and including) the rectum were examined by next‐generation sequencing (NGS), immunohistochemistry, and in situ hybridization. Microsatellite instability (MSI) and tumor mutational burden (TMB) were assessed by NGS. Results: Younger patients ( n = 350), when compared with older patients ( n = 776), showed higher mutation rates in genes associated with cancer‐predisposing syndromes (e.g., Lynch syndrome), such as MSH6 (4.8% vs. 1.2%, p = .005), MSH2 (2.7% vs. 0.0%, p = .004), POLE (1.6% vs. 0.0%, p = .008), NF1 (5.9% vs. 0.5%, p < .001), SMAD4 (14.3% vs. 8.3%, p = .024), and BRCA2 (3.7% vs. 0.5%, p = .002). Genes involved in histone modification were also significantly more mutated: KDM5C (1.9% vs. 0%, p = .036), KMT2A (1.1% vs. 0%, p = .033), KMT2C (1.6% vs. 0%, p = .031), KMT2D (3.8% vs. 0.7%, p = .005), and SETD2 (3.2% vs. 0.9%, p = .039). Finally, TMB‐high (9.7% vs. 2.8%, p < .001) and MSI‐high (MSI‐H; 8.1% vs. 1.9%, p = .009) were more frequent in younger patients. Conclusion: Our findings highlight the importance of genetic counseling and screening in younger CRC patients. MSI‐H and TMB‐high tumors could benefit from immune‐checkpoint inhibitors, now approved for the treatment of MSI‐H/deficient mismatch repair metastatic CRC patients. Finally, histone modifiers could serve as a new promising therapeutic target. With confirmatory studies, these results may influence our approach to younger adults with CRC. Abstract : To better understand the disease biology and identify molecular targets for young patients with metastatic colorectal cancer, this study explored the effect of age on the tumor biology of left‐sided colorectal cancer. This is the first study to investigate the molecular differences between younger and older adults and aimed to broaden insights into the disease biology and potential biomarkers that might be involved in early onset colorectal cancer.